Transport responses from rate of decay and scattering processes in the Nambu-Jona-Lasinio model - Ghosh, Sabyasachi; Serna, Fernando E. [UNESP]; Abhishek, Aman; Krein, Gastão [UNESP]; Mishra, Hiranmaya (American Physical Society (APS), 2019)
We have calculated quark and antiquark relaxation time by considering different possible elastic and inelastic scatterings in the medium. Comparative roles of these elastic and inelastic scatterings on different transport coefficients are explored. The quark-meson effective interaction Lagrangian density in the framework of the Nambu-Jona-Lasinio model is used for calculating both types of scatterings. Owing to a kinetic threshold, inelastic scatterings can only exist beyond the Mott line in the temperature and chemical potential plane, whereas elastic scatterings occur in the entire plane. Interestingly, the strength of inelastic scatterings near and above the Mott line becomes so strong that the medium behaves like a perfect fluid, in that all transport coefficients become very small.